(3WHbGJ GdeLJgOjfs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3CMeO Hf Ydi CHh HcQ GdQGRi GdeYQha HGdLUGU s
(3Vef eLehY , JQJjHgG (B: (3ef U (B150 - (3U(B158s
(3WHbGJ ai ePgH GdMfajIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B449 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B176 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdGScfOQjI (B(3658(3L(B(8)) s
Keywords: (3GdJGQjNs